The Effect Of Motivation And Internship Experience On Culinary Students’ Work Readiness At Vocational High School - Maharani, Nindi Putri; Handajani, Sri; Nurfatimah, Ratna Palupi; Romadhoni, Ita Fatkhur (Universitas Negeri Padang, 2025)
This study aims to analyze the influence of motivation and internship (PKL) experience on the work readiness of culinary students at SMK Negeri 8 Surabaya. Grounded in Maslow’s hierarchy of needs and Kolb’s experiential learning theory, both factors are considered essential components in shaping students’ employability. This research employed a quantitative correlational method with a sample of 62 eleventh-grade culinary students selected through random sampling. Data were collected using a Likert-scale questionnaire and analyzed through multiple linear regression using SPSS 26. The results indicate that motivation and internship experience have a positive and significant effect on students’ work readiness, both partially and simultaneously. The regression model produced an Adjusted R² value of 0.583, indicating that 58.3% of the variance in work readiness is explained by the two predictor variables.